2022
DOI: 10.1186/s13019-021-01749-8
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic lobectomy versus open lobectomy in the treatment of large lung cancer: propensity-score matched analysis

Abstract: Background There are several concerns on thoracoscopic surgery for large tumors because of the increased risk of tumor cell spillage. This study aimed to compare perioperative outcomes and oncological validity between video-assisted thoracoscopic surgery (VATS) and open lobectomy for non-small cell lung cancer (NSCLC) with tumor size > 5 cm. Methods We retrospectively reviewed 355 patients who underwent lobectomy with clinical N0 NSCLC with soli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Similar to our study, Karasaki et al previously reported that cVATS preserved the reduction of the latissimus dorsi mass more than open thoracotomy at 1 year after surgery: 43% reduction of the latissimus dorsi mass with open thoracotomy and 11% with cVATS on the surgical side 29 . cVATS has been reported to be a technique that maintains fewer respiratory complications, shorter hospital stay, lower mortality, less pain and better postoperative QOL than open chest surgery without compromising oncological outcomes 30–33 . Charloux et al reported that the postoperative loss of FEV1 was 9% for segmentectomy through an open thoracotomy and 5% for segmentectomy through cVATS 8 .…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our study, Karasaki et al previously reported that cVATS preserved the reduction of the latissimus dorsi mass more than open thoracotomy at 1 year after surgery: 43% reduction of the latissimus dorsi mass with open thoracotomy and 11% with cVATS on the surgical side 29 . cVATS has been reported to be a technique that maintains fewer respiratory complications, shorter hospital stay, lower mortality, less pain and better postoperative QOL than open chest surgery without compromising oncological outcomes 30–33 . Charloux et al reported that the postoperative loss of FEV1 was 9% for segmentectomy through an open thoracotomy and 5% for segmentectomy through cVATS 8 .…”
Section: Discussionsupporting
confidence: 88%
“…First, few lung cancer patients underwent open surgery, resulting in a lower frequency of PPCs, which may preclude the observation of a large group in a timely manner and affect the comparability and generalization of the study results. However, VATs have been increasingly applied for LC surgery during the past 10 57 and recent report showed the proportion of VATs was reached 74.9% in LC patients, 58 suggesting that this result can be interpreted for current clinical practice. Second, we used an anchor-based method to find the optimal cutpoint considering the relation between symptom severity and PPCs.…”
Section: Discussionmentioning
confidence: 85%
“…The reader is forced to consult other types of papers in which the operational times in minutes is reported. The muchheralded advantage regarding VATS in-hospital days is counterweighted by the time, in which the patient spends on the operational table in the theater (97). In-hospital stays are loosely related to the actual surgical technicality, connected to other non-operative or even extramedical factors and are famously multifactorial, and ultimately bias sensitive.…”
Section: The Case Of Mythologymentioning
confidence: 99%